Evaluation of the Positivity Rate of the Thick Drops and the Physical Integrity of the Nets Used by the Populations of Zogbo in the Cotonou Commune - Tokponnon, Tatchémè Filémon (My University, 2023)
Background: Malaria is a potentially fatal disease caused by parasites transmitted by the bites of infected female Anopheles mosquitoes. It is a preventable and curable disease. Thus, the use of insecticide-treated mosquito nets is a means of combating malaria. In this context, this study assessed the positivity rate of strawberry drops at the St Vincent de Paul hospital in Zogbo and the physical integrity of mosquito nets used by the population in the same locality. Methods: In order to determine the prevalence of malaria in the Saint Vincent de Paul hospital in Zogbo, we took venous and capillary samples from patients for thick blood tests from 31 May to 19 August 2022. We then interviewed 216 households including 100 positive patients in the Zogbo district in southern Benin over a period from 8 July to 19 August on the physical condition of the nets (torn, sewn, tied, frequency of washing, drying method, etc.) in order to assess their physical integrity. Results: Out of 863 thick drops performed, 686 were positive, representing a positivity rate of 79.49%. The household surveys revealed that the majority of respondents were uneducated married women. Indeed, all households own at least one long-lasting insecticide-treated net of three different brands, namely Dawa net and Olyset net in particular and Permanet 2 and 3. However, all the nets observed were either with holes, tied in several places, loosely tied or sewn in several places. In addition, most households washed their nets three times in three months, a percentage of 66.20%, and 100% of households dried their nets in the sun. Conclusion: This study showed that there is a high prevalence of malaria at St Vincent de Paul Hospital, which is due to the loss of physical integrity of the nets. In addition to industry- prescribed recommendations to reduce malaria mortality and morbidity in endemic areas.
Keywords: Prevalence; Malaria; Physical integrity; Mosquito nets; Zogbo